TEM and XRD structure examination of Sn-doped indium oxide (ITO) - Popović, Jasminka (Array, 2008)
Tin-doped indium oxide (ITO) is an advanced material with many electronic and optical applications due to its high electrical conductivity and transparency to light [1]. These properties are associated both with structure and microstructure [2]. Indium oxide crystallizes in a cubic bixbyite-type structure in space group Ia3  3 . It has 80 atoms in unit cell, where 32 sites are occupied by cations in two non-equivalent six-fold coordinated sites (B and D sites, respectively). With tin doping a charge imbalance is created due to a different valence of indium and tin ions. Sn – 119Mössbauer spectroscopy revealed that incorporated tin resided equally B and D sites for 7.8at% Sn [4]. This work focuses on influence of tin doping to particle size and strain of nanocrystalline In2O3. Powder ITO samples containing 2-14 at% Sn were prepared by a sol-gel technique from InCl3 and SnCl4 reagent grade chemicals, followed by thermal treatment at 300 °C for 2 h. As-prepared samples were additionally annealed at 1000 °C for 1 h and slowly cooled to RT. Both, the as-prepared and the annealed samples were examined by X-ray diffraction (XRD) and transmission electron microscopy (TEM). Diffraction lines were broadened indicating the nanosized crystallites in the samples. The line broadening increased with the tin content in two series of samples, the as-prepared and the annealed samples, broadening being less pronounced for the latter ones. Analysis of line broadening was performed in Rietveld structure refinement by the PANalytical X Pert High Score Plus program. Silicon powder (Koch-Light Lab. Ltd., 99.999% purity) was used as instrument standard. For the as-prepared samples crystallite sizes decreased and strain increased with the increase of tin content. Annealing at 1000 °C promoted a grain growth and lessening of lattice strain for each sample. However, crystallite sizes and lattice strain followed the dependence on tin content as in the as-prepared samples. The inter planar distances, d, in the examined samples determined by the selected area electron diffraction (SAED) were in accordance with XRD data. SAED of the observed regions appear to be nanocrystalline having a bixbyite– type cubic structure giving strong evidence of solid solution formation of indium oxide and tin oxide. TEM studies proved that ITO samples contained nanocrystalline particles/grain sizes. The grain sizes had nearly spherical shape at lower tin doping level, while at higher doping level (>8 at %) they appeared to be elongated. The crystallite sizes measured by TEM well agreed with those obtained by XRD line broadening analysis. HRTEM gave additional insight into the observed microstructure.